The Development of Website Based Jobdesk Document Management System using Agile Method at PT. Pupuk Kujang - Yenni Fatman; Alya Ningrum; Ai Risma Azizah (Compiler, 2023)
Ineffective storage and not recorded neatly are the reasons for making this system. Taking the name Jobdesk itself was chosen because it is a system that aims to make it easier for employees to send Jobdesk document information and can help the input process digitally. This system is also made not limited only to admins and employees, admins can also create new users and give access to the employees who have positions related to this application. This system has been implemented in accordance with the request from the development department and organization of PT Pupuk Kujang. This system is made based on a website using php language with CodeIgniter 3 framework